Some experience on thumb reconstruction using 3D printing technology. Issue 1 (January 2018) - Cong, Rui; Zang, Chengwu; Liang, Chao
We have experience on thumb reconstruction using 3D printing technology in three main aspects. First, 3D printing technology improved accuracy in measuring the reconstructed thumb bone length. Second, we used mirroring technology to obtain the 3D image of normal shape of the injured thumb. Third, we used the bone segment model printed for accurate preoperative design and simulation of the operation. We also used models for preoperative communication. In future work, we plan to focus on the procedures and standardization of the 3D printing technology in thumb reconstruction. We intend to use 3D printing technology in the treatment of congenital hand malformations and to explore micro-3D technology.